Presence of Antibiotic Residues and Antibiotic Resistant Bacteria in Cattle Manure Intended for Fertilization of Agricultural Fields: A One Health Perspective - Judith Huygens; Els Daeseleire; Jacques Mahillon; Daan Van Elst; Johan Decrop; Jurgen Meirlaen; Jeroen Dewulf; Marc Heyndrickx; Geertrui Rasschaert (MDPI AG, 2021)
Antibiotic resistant bacteria and antibiotic residues can enter the environment when using animal manure as fertilizer. Twenty-five mixed beef cattle farmyard manure samples and 9 mixed fattening calf slurry samples from different farms across Belgium were investigated for the presence of 69 antibiotic residues, antibiotic resistant Escherichia coli and Salmonella spp. Doxycycline, oxytetracycline, ciprofloxacin, enrofloxacin, flumequine and lincomycin were detected in all fattening calf slurry samples with mean concentrations of 2776, 4078, 48, 31, 536 and 36 µg/kg manure, respectively. Sulfadiazine was detected at a mean concentration of 10,895 µg/kg. Further, antibiotic residues were found in only 4 of the 25 beef cattle farmyard manure samples. Oxytetracycline was detected twice below 500 µg/kg. Paromomycin, ciprofloxacin and enrofloxacin were detected in a concentration below 100 µg/kg. Of E. coli isolates, 88% and 23% from fattening calf slurry and beef cattle farmyard manure, respectively, were resistant to at least one of the antibiotics tested. Multi-drug resistance was observed at a maximum of 10 and 7 antibiotics, respectively. The occurrence of antibiotic resistant E. coli and antibiotic residues is shown to be higher in fattening calf slurry than in beef cattle farmyard manure used for agricultural field fertilization.